Response of SAOS-2 cells to simulated microgravity and effect of biocompatible sol–gel hybrid coatings. (May 2016) - Catauro, M.; Bollino, F.; Papale, F.
Abstract: The health of astronauts, during space flight, is threatened by bone loss induced by microgravity, mainly attributed to an imbalance in the bone remodeling process. In the present work, the response to the microgravity of bone cells has been studied using the SAOS-2 cell line grown under the condition of weightlessness, simulated by means of a Random Positioning Machine (RPM). Cell viability after 72 h of rotation has been evaluated by means of WST-8 assay and compared to that of control cells. Although no significant difference between the two cell groups has been observed in terms of viability, F-actin staining showed that microgravity environment induces cell apoptosis and altered F-actin organization. To investigate the possibility of hindering the trend of the cells towards the death, after 72 h of rotation the cells have been seeded onto biocompatible ZrO2 /PCL hybrid coatings, previously obtained using a sol–gel dip coating procedure. WST-8 assay, carried out after 24 h, showed that the materials are able to inhibit the pro-apoptotic effect of microgravity on cells. Highlights: SAOS-2 line cells were grown under 0 g conditions, simulated by a desktop RPM. Microgravity induces the alteration of the F-actin filament arrangement. The cytoskeleton alteration leads to the apoptosis of SAOS-2 cells. Biocompatible ZrO2 /PCL hybrids coatings were prepared by sol–gel dip coating method. The growth on hybrid coatings inhibits the 0 g-induced pro-apoptotic effect on cells.